Genetic association in chronic periodontitis through dermatoglyphics: An unsolved link? - Sowmya Astekar; Vineet Garg; Madhusudan Astekar; Ashutosh Agarwal; Aditi Murari (Wolters Kluwer Medknow Publications, 2017)
Introduction: Because dermatoglyphic features are strongly affected by genetic and environmental factors, using it as supportive evidence in the diagnosis of hereditary disorders becomes a reality. Offspring of patients suffering from chronic periodontitis have a high prevalence rate of periodontal breakdown, suggesting strong familial influence. Aims: The present study intends to evaluate and compare the dermatoglyphic patterns in controls and periodontally compromised patients. Settings and Design: A hospital based cross-sectional study was conducted, including a total of 60 individuals, divided into study and control groups of 30 each. The study group included clinically diagnosed periodontitis patients.Materials and Methods: The digital prints were collected using biometric scanner and palmer prints using digital flatbed scanner. Care was taken to ensure that full prints of ridges were obtained. The periodontal status of all 60 participants was assessed clinically for attachment level and pocket depth. Later, Russell's periodontal index was also calculated. Statistical Analysis: The data obtained was subjected to statistical analysis using chi square and Student's t-test. Results: Among the finger ridge patterns, whorl pattern was found to be the most common in the study group whereas loop pattern was the most common in the control group. Mean total finger ridge count in the study group (165.69 ± 25.30) was significantly higher (P = 0.001) than the control group (125.4 ± 16.38). Mean dat angle was significantly higher (P = 0.039) in the study group (60.60 ± 2.76) than the control group (59.20 ± 2.62). Conclusion: Dermatoglyphics may serve as an early predictor in identifying high risk group individuals of developing diseases like periodontitis.